2020
DOI: 10.1186/s12936-020-03360-z
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of extracellular vesicles-derived microRNAs in Thai malaria patients

Abstract: Background: Extracellular vesicles (EVs) have been broadly studied in malaria for nearly a decade. These vesicles carry various functional biomolecules including RNA families such as microRNAs (miRNA). These EVs-derived microR-NAs have numerous roles in host-parasite interactions and are considered promising biomarkers for disease severity. However, this field lacks clinical studies of malaria-infected samples. In this study, EV specific miRNAs were isolated from the plasma of patients from Thailand infected w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Protectively packaged into EVs, miRNAs are now known to play vital roles in protozoan and other infectious diseases [ 63 , 64 ]. Plasmodium infection evidently alters miRNA expression, as distinct plasma EV-miRNA profiles in murine malaria models [ 58 ] and human malaria [ 60 ] have been identified. In EVs from P. berghei ECM, the expression of miR-146a and miR-193b was found to be significantly dysregulated compared to EVs in Plasmodium yoelii non-CM and non-infected mice; while miR-146a was markedly upregulated in EVs, miR-193b was downregulated [ 58 ].…”
Section: The Pathogenesis Of Malaria: a Potential Role For Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protectively packaged into EVs, miRNAs are now known to play vital roles in protozoan and other infectious diseases [ 63 , 64 ]. Plasmodium infection evidently alters miRNA expression, as distinct plasma EV-miRNA profiles in murine malaria models [ 58 ] and human malaria [ 60 ] have been identified. In EVs from P. berghei ECM, the expression of miR-146a and miR-193b was found to be significantly dysregulated compared to EVs in Plasmodium yoelii non-CM and non-infected mice; while miR-146a was markedly upregulated in EVs, miR-193b was downregulated [ 58 ].…”
Section: The Pathogenesis Of Malaria: a Potential Role For Evsmentioning
confidence: 99%
“…In EVs from P. berghei ECM, the expression of miR-146a and miR-193b was found to be significantly dysregulated compared to EVs in Plasmodium yoelii non-CM and non-infected mice; while miR-146a was markedly upregulated in EVs, miR-193b was downregulated [ 58 ]. In humans, when compared with uninfected individuals, the miRNA hsa-let-7a-5p was upregulated in EVs from patients with falciparum and vivax malaria, while miRNAs hsa-miR-150-5p and hsa-miR-15b-5p were both upregulated in vivax malaria alone [ 60 ]. These and other miRNAs have already been implicated in other neurological diseases and were predicted to be of importance in pathways relevant to malaria, such as EV biogenesis, inflammation, cytoadhesion, [ 58 ], adherens junction and transforming growth factor (TGF)-β pathways [ 60 ].…”
Section: The Pathogenesis Of Malaria: a Potential Role For Evsmentioning
confidence: 99%
“…In Zofia Wicik et al 63 showed that this miRNA could regulate ACE2 networks. Moreover, this miRNA can link the pathogenesis of HIV-1 and malaria 64 66 . Similarly, Jianghong Wei et al 67 found that overexpression of miR-16 inhibited the growth and metastasis of the DMS-53 lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…hsa-miR-16-5p was found to affect a phenotypic change of T cells, modulate inflammatory signalling and cytokines including IL-1β, IL-6 and TNF-α, NF-κB mTOR-related pathways and genes [103,104]. Additionally, MiR-16-5p has been linked with the pathogenesis of several infectious diseases such as HIV-1 infection and malaria [105107]. It is worth mentioning that miR-16-5p as a plasma diagnostic biomarker is able to distinguish severe and mild viral infections [108] and early HIV-1 infection from healthy individuals [106,109].…”
Section: Discussionmentioning
confidence: 99%